2000
DOI: 10.1246/cl.2000.922
|View full text |Cite
|
Sign up to set email alerts
|

Highly Conductive Room Temperature Molten Salts Based on Small Trimethylalkylammonium Cations and Bis(trifluoromethylsulfonyl)imide

Abstract: The electrochemically stable and relatively high conductive room temperature molten salts (RTMS) have been obtained with the use of small ammonium cations such as methoxymethyltrimethylammonium and bis(trifluoromethylsulfonyl)imide. The RTMS showed high conductivity (4.7 mS cm−1 at 25 °C) which is the highest value of all the ammonium based RTMS reported so far.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
176
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 322 publications
(188 citation statements)
references
References 7 publications
11
176
1
Order By: Relevance
“…22 The relationship between lithium dendrite formation and the ionic transport properties of the composite polymer electrolyte is also discussed. 35 Matsumoto et al 36 reported that the LiTFSI ionic liquid in PP13TFSI enables the reversible plating-stripping of lithium metal. Figure 13 shows typical impedance profiles for the Li/ PEO 18 LiTFSI/Li and Li/PEO 18 LiTFSI-1.44PP13TFSI/Li cells at 60°C as a function of the storage time.…”
Section: ¹2mentioning
confidence: 99%
“…22 The relationship between lithium dendrite formation and the ionic transport properties of the composite polymer electrolyte is also discussed. 35 Matsumoto et al 36 reported that the LiTFSI ionic liquid in PP13TFSI enables the reversible plating-stripping of lithium metal. Figure 13 shows typical impedance profiles for the Li/ PEO 18 LiTFSI/Li and Li/PEO 18 LiTFSI-1.44PP13TFSI/Li cells at 60°C as a function of the storage time.…”
Section: ¹2mentioning
confidence: 99%
“…They found that not only the physical but also the electrochemical properties of the ILs depend mainly on the type of anions and cations . Also it was found that the introduction of alkoxy groups into the ILs might lower the viscosity hence increase the effectiveness of the battery based on such liquid (Matsumoto, 2000). The electrochemical windows, feasibility of ILs and the cycle life of batteries prepared with ILs were studied by Yang and co-workers (Xu, 2006).…”
Section: Ionic Liquids Used In Batteriesmentioning
confidence: 99%
“…On the other hand, some papers have been published on the use of aliphatic quaternary ammonium-based ionic liquids, which would be expected to have a higher cathodic stability; this is due to the fact that the small size aliphatic quaternary ammoniumbased ionic liquid has a relatively high melting temperature, compared with the aromatic ones. MacFarlane and co-workers reported that aliphatic quaternary ammonium cations which had relatively short (C1-C4) alkyl chains could not easily form an ionic liquid near room temperature , as cited in Sun et al,1997,1998a,1998b& MacFarlane et al,1999,2000. However, Angell and co-workers and Matsumoto et al reported that some asymmetric and short-chain aliphatic quaternary ammonium cations with a methoxyethyl or methoxymethyl group on the nitrogen atom formed ionic liquids below room temperature (Cooper & Angell,1986;Emanuel et al,2003) (Matsumoto et al,2000(Matsumoto et al, ,2001(Matsumoto et al, ,2002 Fig.…”
Section: Introductionmentioning
confidence: 97%